2020
DOI: 10.1007/s12155-020-10217-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Extraction Solvents on Oil Extracted from Jatropha Seeds and the Potential of Seed Residues as a Heat Provider

Abstract: The present study focuses on the determination of oil contents of thirteen different jatropha seed collections from Ethiopia. The oil was extracted with a Soxhlet extractor using n-hexane which was selected out of four different solvents: diethyl ether, ethanol, n-heptane, and n-hexane. Cotton and thimble were used as filter for the extractions. Some properties of the oil of Chali seed collection and a sample of mixed oils (a mixture of equal volume of oils from thirteen different seed collections) were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 43 publications
1
22
0
1
Order By: Relevance
“…The seed meal from each individual sample were extracted by n-hexane (95% purity), ethanol (99% purity) and methanol/chloroform (50:50) (>99% purity) solvents ( Keneni et al., 2020 ; Tsakins et al., 1999 ). The solvent extraction process was carried out using 200ml soxhlet apparatus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The seed meal from each individual sample were extracted by n-hexane (95% purity), ethanol (99% purity) and methanol/chloroform (50:50) (>99% purity) solvents ( Keneni et al., 2020 ; Tsakins et al., 1999 ). The solvent extraction process was carried out using 200ml soxhlet apparatus.…”
Section: Methodsmentioning
confidence: 99%
“…The solvent extraction process was carried out using 200ml soxhlet apparatus. About 20g of the ground meal of a particular particle size was subjected individually to the solvent extraction for a particular time duration as contained in Table 1 and temperature of 69 °C, 78 °C and 70 °C for hexane, ethanol and methanol/chloroform solvents respectively ( Keneni et al., 2020 ). The oil solutions were filtered and subjected to distillation using rotary evaporator.…”
Section: Methodsmentioning
confidence: 99%
“…Sayyar et al [28] while working on similar oil extractions reported oil yields of 47.3% and 46% w/w for n-hexane and petroleum ether, respectively, for solvent-to-solid ratio of 6 : 1 and 8h extraction time. Slightly higher values of optimum oil yields have been reported by Keneni et al [24] (48.29% w/w), Adeyinka [22] (56.69% w/w), and Yusuff [29] (56.69% w/w) while working with n-hexane for the similar materials. ese variations could be due to the various cultivars of Jatropha plant.…”
Section: 4mentioning
confidence: 74%
“…Solvent extraction methods have been reported to provide improved oil recoveries in the range of 90 to 99% [21][22][23][24][25][26]. e oil recovery by using this method depends on many parameters such as the type of the solvent used, reaction time, temperature, particle size of the meal, and solvent-to-meal ratio.…”
Section: Introductionmentioning
confidence: 99%
“…were used traditionally for treatment of diabetes mellitus. 17 Considering traditional claims, present study was undertaken to evaluate antidiabetic activity by in vitro approach and investigate the probable mechanism of Ficus Lacor Buch. Ham.…”
Section: Introductionmentioning
confidence: 99%